Divergences 3. : un tournant décisif - Wescher, Herta (Paris : Galerie Arnaud, 1955)
Alcopley, Lewin ; Barré, Martin ; Bergman, Anna-Eva ; Bertrand, Huguette-Arthur ; Canogar, Rafael ; Carrade, Michel ; Coppel, Jeanne ; Dahmen, Karl Fred ; Damian, Horia ; Deyrolle, Jean ; Downing, Joseph Dudley ; Dumitresco, Natalja ; Feito, Luis ; Fichet, Pierre ; Gauthier, Oscar ; Gilioli, Emile ; Goebel ; Guitet, James ; Van Haardt, Georges ; Istrati, Alexandre ; Jacobsen, Robert ; Jonas ; Kalinowski, Horst Egon ; Karskaya, Ida ; Koenig, John ; Laubiès ; Longobardi, Xavier ; Maussion, Charles ; Milo, Jean ; Moser, Wilfrid ; de Panafieu, Jacques ; Pillet, Edgard ; Pouget, Marcel ; Riviera, Lago Antonio Lago ; Schnabel, Day ; Tryggvadottir, Nina
biografie
Frans
boek